A Chiral Copper Catalyzed Site‐Selective O‐Alkylation of Carbohydrates. Issue 3 (29th November 2021) - Ren, Bo; Wang, Jiaxi; Zhang, Mengyao; Chen, Yue; Zhao, Wei
Abstract: Highly regioselective alkylation of sugar hydroxyl groups has always been an important challenge in carbohydrate chemistry, especially for the selective alkylation of trans diols, there is no direct and efficient catalytic method so far. A chiral copper catalyzed universal highly site‐selective alkylation of trans‐diols method is realized. This reaction is performed under mild conditions and has broad substrate scope. The selectivity of the reactions can be controlled by adjusting the copper reagents and the chiral ligands. This method was also applied to the site‐selective modification of drugs and natural products. Abstract :